PENGARUH PENAMBAHAN TEPUNG JAMUR TIRAM PUTIH (Pleurotus ostreareus) TERHADAP KADAR AIR DAN PERSENTASE PRODUK SOSIS DAGING ITIK PETELUR AFKIR - Prasetiyo, Oki; Rahardjo, Agustinus Hantoro Djoko; Rosidi, Rosidi (ANGON: Journal of Animal Science and Technology, 2020)
Background. The study aimed to finding out the effect of the addition of white oyster mushroom flour to the value of water content and the percentage of rejected laying duck sausage meat products. Materials and Methods. The used material female Tegal Ducks meats, white oyster mushroom flour and spices. The study was conducted at the Laboratory of Animal Product Technology, Faculty of Animal Husbandry, Jenderal Soedirman University, Purwokerto with an experimental research method by using a Completely Randomized Design (CRD) with 5 treatments and 4 replications so that 20 experimental units were obtained by Honestly Significant Difference (HSD) further testing. The observed variables in the study were water content and product percentage. The tested treatments consisted of P0: sausage without the addition of white oyster mushroom flour, P1: sausage + white oyster mushroom flour 5% from meat, P2: sausage + white oyster mushroom flour 10% from meat, P3: sausage + white oyster mushroom flour 15 % of meat, and P4: sausage + white oyster mushroom flour 20% of meat. Results. The average water content of sausage from laying duck eggs P0, P1, P2, P3, and P4 was 65,64%; 64,61%; 63,66%; 62,50% and 60,78%. The average percentage products rejected laying duck sausage meat P0, P1, P2, P3, and P4 was 91,81%; 94,46%; 95,41%; 98.07% and 97,58%. Conslusion. Based on the results, it can be concluded that the addition of white oyster mushroom flour in the manufacture of rejected laying duck sausages can reduce water content and increase the percentage of sausage products with the best percentage of 15%.